A Critique of the Moral Optimism of Sam Harris: Polemical Comments - Szocik, Konrad (Studia religiologica, 2014)
Sam Harris, one of the new atheists, believes that science is an authority in moral issues. Science can help us understand what our moral duties are, and what is right and wrong in a moral sense. However, the cultural and historical diversity of human behaviours, especially the history of wars and conflicts, suggests that it is difficult to show one, common and universal kind of morality. Here we show that Harris’s moral theory is a particular project which could not be “scientifically” justifi-able.